Understanding tensions and identifying clinician agreement on improvements to early-stage chronic kidney disease monitoring in primary care: a qualitative study. Issue 3 (17th March 2016) - Simmonds, Rosemary; Evans, Julie; Feder, Gene; Blakeman, Tom; Lasserson, Dan; Murray, Elizabeth; Bennert, Kristina; Locock, Louise; Horwood, Jeremy
Abstract : Objectives: Since 2006, general practitioners (GPs) in England, UK, have been incentivised to keep a register and monitor patients with chronic kidney disease (CKD) stages 3–5. Despite tensions and debate around the merit of this activity, there has been little qualitative research exploring clinician perspectives on monitoring early-stage CKD in primary care. This study aimed to examine and understand a range of different healthcare professional views and experiences of identification and monitoring in primary care of early-stage CKD, in particular stage 3. Design: Qualitative design using semistructured interviews. Setting: National Health Service (NHS) settings across primary and secondary care in South West England, UK. Participants: 25 clinicians: 16 GPs, 3 practice nurses, 4 renal consultants and 2 public health physicians. Results: We identified two related overarching themes of dissonance and consonance in clinician perspectives on early-stage CKD monitoring in primary care. Clinician dissonance around clinical guidelines for CKD monitoring emanated from different interpretations of CKD and different philosophies of healthcare and moral decision-making. Clinician consonance centred on the need for greater understanding of renal decline and increasing proteinuria testing to reduce overdiagnosis and identify those patients who were at risk of progression and further morbidity and who would benefit from early intervention. Clinicians recommended adopting a holistic approach for patients with CKD representing a barometer of overall health. Conclusions: The introduction of new National Institute for Health and Care Excellence (NICE) CKD guidelines in 2014, which focus the meaning and purpose of CKD monitoring by increased proteinuria testing and assessment of risk, may help to resolve some of the ethical and moral tensions clinicians expressed regarding the overmedicalisation of patients with a CKD diagnosis.